Dynamic response of aluminium matrix syntactic foams subjected to high strain-rate loadings. (1st January 2023) - Alteneiji, M.; Krishnan, K.; Guan, Z.W.; Cantwell, W.J.; Zhao, Y.; Langdon, G.
Highlights: The dynamic response of aluminium matrix syntactic foams subjected to strain-rate above 1000 s −1. The dynamic loading regimes cover SHPB, ballistic and blast. The FE models are developed to simulate the damage profiles of the foam panels. The validated FE models are used to predict oblique impact behaviour of the foam. The results will be useful to assist design such the syntactic foams. Abstract: This paper presents experimental work to characterise the dynamic behaviour of aluminium matrix syntactic foams subjected to compression, Split Hopkinson Pressure Bar and terminal ballistic impact tests as well as blast loading. Numerical models have also been developed to simulate the dynamic response of the composite foams. The effect of strain-rate on their compressive crush behaviour has been investigated, given that the rate-dependent characteristics of these materials are required for designing dynamically loaded structures. Characterisation of the behaviour of the foam under high strain-rate loadings and the identification of the underlying failure mechanisms were also undertaken to evaluate their effective mechanical performance. The results show that the aluminium syntactic foam is sensitive to strain-rate in terms of initial stiffness, peak stress and plateau stress and show a pronounced high-rate dependence at a strain rate above 1000 s-1. The concrete damage plasticity model with rate-dependent features were used to simulate the dynamic behaviour of the foams, with the failure modes being captured. The model was verified and validated against the experimental results, and predictions were made for the normal and oblique ballistic impact response. Overall, the level of agreement between the numerical simulations and the experimental results is encouraging.